2020
DOI: 10.1532/hsf.3015
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Detection of Epicardial Adipose Tissue Combined With Ischemic Modified Albumin in the Diagnosis of Coronary Heart Disease

Abstract: Objective: To evaluate the value of epicardial adipose tissue (EAT) thickness combined with serum ischemic modified albumin (IMA) concentration in the diagnosis of coronary heart disease. Methods: A total of 180 patients with coronary heart disease from May 2017 to December 2018 were selected as the case group. After the examination of Judkins coronary angiography, they were grouped according to the results of angiography, including 60 patients in a single-vessel group, 60 patients in a double-vessel g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…All the search results were evaluated according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [ 26 ]. The diagnostic criteria for coronary heart disease established by the World Health Organization are: at least 1 coronary artery stenosis ≥ 50% in the right coronary artery, left main trunk, anterior descending or circumflex artery and its main branches [ 27 , 28 ]. In the single−vessel disease group, coronary artery stenosis was ≥50%.…”
Section: Methodsmentioning
confidence: 99%
“…All the search results were evaluated according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement [ 26 ]. The diagnostic criteria for coronary heart disease established by the World Health Organization are: at least 1 coronary artery stenosis ≥ 50% in the right coronary artery, left main trunk, anterior descending or circumflex artery and its main branches [ 27 , 28 ]. In the single−vessel disease group, coronary artery stenosis was ≥50%.…”
Section: Methodsmentioning
confidence: 99%
“…It can be used to examine diseases such as cardiovascular system, nervous system lesions, and thoracic lesions. It has high diagnostic accuracy but is expensive [13][14][15]. Echocardiography can clearly display the structure and movement of the heart, blood flow velocity, etc., and record the images of sound waves that are transmitted to the heart and return.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that EAT is closely related to the occurrence of coronary atherosclerosis, and may be a new risk factor for CHD. [1][2][3] The measurements of EAT include ultrasound, [4][5][6] and CT. 8 CT imaging technology is currently the preferred method for measuring EAT in clinics, and it can achieve accurate quantitative measurement of the total volume of EAT. Therefore, using CT technology to explore the volume changes of the EAT in CHD patients is of great significance for the early prevention of CHD and the subsequent effective treatment.…”
Section: Introductionmentioning
confidence: 99%